Analysis of the Profitability and Feasibility of Patchouli Farming in a Polyculture System in Lembah Subur Village, Dangia Subdistrict, East Kolaka Regency - Kifli, Silvan; Rianse, Ilma Sarimutaqiyma; Indarsyih, Yusna (International Journal of Technology and Education Research, 2026)
This study aims to analyze the condition of patchouli farming, the level of profit obtained, and the feasibility of patchouli farming in Lembah Subur Village, Dangia Subdistrict, East Kolaka Regency. The research was conducted from August 2025 to January 2026 using a descriptive quantitative method. Data used in this study consisted of primary data obtained through direct interviews with patchouli farmers and secondary data collected from village records and relevant institutions. The number of respondents was 34 farmers selected from a population of 50 using the Slovin formula. The results show that patchouli farming in Lembah Subur Village is still managed using traditional cultivation techniques. The average production cost incurred by farmers was Rp1,522,000 per planting season, while the average total revenue reached Rp8,849,118. The average profit obtained by farmers was Rp7,327,118 per hectare per planting season. The feasibility analysis shows an R/C Ratio of 5.81, indicating that patchouli farming is economically feasible and profitable to develop